Pengaruh Digital Marketing, Brand Awareness dan Kepercayaan Terhadap Loyalitas Pelanggan Barenbliss: Studi Kasus Mahasiswa di Kabupaten Jember - Dea Yuniar Firdaus; Achmad Hasan Hafidzi; Wahyu Eko Setianingsih (Universitas Nusantara PGRI Kediri, 2025)
Current technological developments make consumers carry out activities to buy goods through digital media, so that it can provide convenience for its users. Like currently, female students are a group that often shop online. In addition to making purchases with digital media, it can make it easier to do marketing such as promotions or find information. With the many skincare or make-up sellers currently using hazardous chemicals, with digital marketing we can find out more information before buying a product. So that we can become aware of the brand and trust the brand more. Barenbliss is a brand that is quite good at utilizing digital marketing. This study aims to investigate and analyze the influence of digital marketing, brand awareness, and the level of trust that has a major impact on Barenbliss customer loyalty. The type of research conducted is quantitative research with a population of female students in Jember Regency. In this study, the sample taken consisted of 400 respondents. The conclusion of this study shows that digital marketing, brand awareness, and trust have a significant influence on customer loyalty.